2008
DOI: 10.1038/ng.112
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified prion linked to the chromatin-remodeling factor Swi1 in Saccharomyces cerevisiae

Abstract: SWI/SNF, an evolutionarily conserved ATP-dependent chromatin-remodeling complex, has an important role in transcriptional regulation 1 . In Saccharomyces cerevisiae, SWI/SNF regulates the expression of ~6% of total genes through activation or repression 2 . Swi1, a subunit of SWI/SNF, contains an N-terminal region rich in glutamine and asparagine, a notable feature shared by all characterized yeast prions-a group of unique proteins capable of self-perpetuating changes in conformation and function 3 . Here we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
290
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(299 citation statements)
references
References 30 publications
7
290
2
Order By: Relevance
“…In sum, since [SWI + ] was previously shown to rely upon the activity of the disaggregating ATPase Hsp104 for propagation, 11 it was not surprising to find that the other core components of …”
Section: Correlations Among Yeast Prionsmentioning
confidence: 97%
See 1 more Smart Citation
“…In sum, since [SWI + ] was previously shown to rely upon the activity of the disaggregating ATPase Hsp104 for propagation, 11 it was not surprising to find that the other core components of …”
Section: Correlations Among Yeast Prionsmentioning
confidence: 97%
“…The uninduced rate of [PSI + ] formation, that is, the rate uninfluenced by protein overexpression or environmental stresses, was recently reported to be 5.7 x 10 -7 /cell/generation. 25 In contrast, some, if not all, of the N-rich prions discussed above form at much higher rates ( Table 2 11 While they note that they tried the experiment several times before succeeding, the ability to detect spontaneous [SWI + ] formation from a relatively small yeast cell population strongly suggests that [SWI + ] appears significantly more often than [PSI + ], which would only be expected to appear at a rate of 5 out of 10,000,000 ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Implications Of Prion Instabilitymentioning
confidence: 97%
“…However, unlike mammalian prions, yeast prions do not result in cell death, but instead act as heritable, protein-based genetic elements, conferring on the cell new phenotypic traits that are propagated epigenetically (6,7). Although work over the last 15 years has uncovered a growing number of prions and prospective prion proteins in evolutionarily divergent members of the fungal kingdom (8)(9)(10)(11)(12)(13)(14), it is not yet known how pervasive prions are in nature; more specifically, it is not known whether bacteria contain prions or whether the bacterial cytoplasm can support the formation of prions. The study of yeast prions has revealed an essential interplay between prion proteins and cellular chaperone proteins (15,16); thus, it is of particular interest to learn whether the bacterial chaperone environment is permissive for the formation of prion-like aggregates.…”
mentioning
confidence: 99%
“…88 Also, [SWI C ] manifests not only beneficial, but also harmful phenotypes: it inhibits vegetative growth on media containing non-fermentable carbon sources. 40 This might mean that these prions are egoistic elements or even that they are harmful. However, we cannot exclude the possibility that these prions provide a survival advantage under certain conditions that occur rarely and which we do not yet know, and thus act as bet hedging prions.…”
Section: ¡12mentioning
confidence: 99%
“…While opinions still differ on whether the majority of yeast prions are functional epigenetic modifiers, egoistic elements or diseases, most of them do not have a significant negative effect on fitness and can be maintained in yeast populations for a long time, or even indefinitely. 33,34 To date there are nine known amyloid-based yeast prions, [PSI C ] 35 (for which structural protein is Sup35), 36 [URE3] 37 (Ure2), 36 [PIN C ] (Rnq1), 38,39 [SWI C ] (Swi1), 40 [OCT C ] (Cyc8), 41 [MOT3 C ] (Mot3), 14 [ISP C ] (Sfp1), 42 [NUP100 C ] (Nup100), 43 [MOD C ] (Mod5), 44 as well as two functional prion-like amyloids:…”
Section: Introductionmentioning
confidence: 99%